2022
DOI: 10.1002/aenm.202202993
|View full text |Cite
|
Sign up to set email alerts
|

Air Instability of Ni‐Rich Layered Oxides–A Roadblock to Large Scale Application

Abstract: Benefiting from the excellent lithium ions diffusion kinetics and considerable discharge specific capacity, Ni‐rich layered oxides have become the preferred selection cathode active materials (CAMs) for high energy density Li‐ion batteries. However, due to the distinctive electronic structure of nickel ions (Ni2+/3+/4+) and the strict criteria for sintering conditions, the Ni‐rich CAMs inherently suffer from notorious deterioration when in contact with the ambient air. This review provides a comprehensive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 138 publications
0
15
0
Order By: Relevance
“…The formation of residual Li species is attributed to the instability of Ni 3+ in ambient air. As illustrated in Figure 6a, CO 2 and H 2 O can react with the cathode, forming a surface residual Li outer layer and a Li‐deficient rock‐salt NiO layer due to the loss of O 2 and reduction of Ni 3+ to Ni 2+ [55, 56] . The content of surface residual Li, typically measured by an acid‐base titration method, has been demonstrated to increase exponentially with the Ni content [4] .…”
Section: Outgassing Of High‐ni Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of residual Li species is attributed to the instability of Ni 3+ in ambient air. As illustrated in Figure 6a, CO 2 and H 2 O can react with the cathode, forming a surface residual Li outer layer and a Li‐deficient rock‐salt NiO layer due to the loss of O 2 and reduction of Ni 3+ to Ni 2+ [55, 56] . The content of surface residual Li, typically measured by an acid‐base titration method, has been demonstrated to increase exponentially with the Ni content [4] .…”
Section: Outgassing Of High‐ni Cathodesmentioning
confidence: 99%
“…As illustrated in Figure 6a, CO 2 and H 2 O can react with the cathode, forming a surface residual Li outer layer and a Li-deficient rock-salt NiO layer due to the loss of O 2 and reduction of Ni 3 + to Ni 2 + . [55,56] The content of surface residual Li, typically measured by an acid-base titration method, has been demonstrated to increase exponentially with the Ni content. [4] The accumulation of LiOH and Li 2 CO 3 can be observed through in situ transmission electron microscopy (TEM, Figure 6b).…”
Section: Formation and Decomposition Of Surface Residual LI Speciesmentioning
confidence: 99%
“…However, water washing may damage the surface structure of the material, 30 while heat treatment further increases energy consumption and cannot compensate for the loss of lithium due to cation exchange. 31 The main purpose of the elemental doping strategy is to improve stability by creating stronger covalent bonds between the lattice oxygen and the dopant ions or by reducing the amount of surface active trivalent nickel on the surface. In addition, researchers have tried to construct a passivation layer with stable chemical properties on the surface of Ni-rich cathode material particles to block harmful side reactions caused by the contact of positive material particles with air, which is widely considered an effective strategy to improve air stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Both water washing and heat treatment can remove impurities, including residual lithium compounds and other adsorbed substances, from the surface of Ni-rich Co-less cathode materials to some extent. However, water washing may damage the surface structure of the material, while heat treatment further increases energy consumption and cannot compensate for the loss of lithium due to cation exchange . The main purpose of the elemental doping strategy is to improve stability by creating stronger covalent bonds between the lattice oxygen and the dopant ions or by reducing the amount of surface active trivalent nickel on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many scholars have gradually realized the importance of storage properties of SCNCM in the process of industrialization and have started to explore the degradation mechanism of the electrochemical performance. First, research shows that the main challenge in the storage process is the aggravation of Li/Ni mixing owing to the spontaneous reaction caused by high reactivity of Ni 3+ and its inevitable contacts with air. , Second, the Li on SCNCM surface reacting with O 2 and CO 2 forms a variety of Li-ion compounds, which increases with the rising storage time. The residual Li on SCNCM surface fastens the transformation from a layered structure to a rock-salt phase, and Li-ion (de)­intercalation during charge/discharge process is blocked due to the presence of Li-ion compounds. , In addition, the air humidity also poses a great impact on the structural stability of SCNCM. The contacts between H 2 O and SCNCM increases the potential of H + /Li + exchange, which leads to the loss of Li from the lattice site. Furthermore, studies unveils that a new phase Li 1– x H x NiO 2 forms after the contacts, which compresses the Li–O interlayer space and makes the Li-ion diffusion channel get shrunk. , Fang et al explored the effect of the percentage of different crystal planes and water concentration on the formation of surface impurities; they found that various crystal planes on the SCNCM surface illustrated different adsorption capabilities for O 2 and CO 2 and the obtained impurities were also varied. In addition, the repair of SCNCM after storage is another research focus.…”
Section: Introductionmentioning
confidence: 99%